Canadian Thoracic Society Recommendations for Management of Chronic Obstructive Pulmonary Disease – 2007 Update. (2007) - O'Donnell, Denis E; Aaron, Shawn; Bourbeau, Jean; Hernandez, Paul; Marciniuk, Darcy D; Balter, Meyer; Ford, Gordon; Gervais, Andre; Goldstein, Roger; Hodder, Rick; Kaplan, Alan; Keenan, Sean; et al.
Abstract : Chronic obstructive pulmonary disease (COPD) is a major respiratory illness in Canada that is both preventable and treatable. Our understanding of the pathophysiology of this complex condition continues to grow and our ability to offer effective treatment to those who suffer from it has improved considerably. The purpose of the present educational initiative of the Canadian Thoracic Society (CTS) is to provide up to date information on new developments in the field so that patients with this condition will receive optimal care that is firmly based on scientific evidence. Since the previous CTS management recommendations were published in 2003, a wealth of new scientific information has become available. The implications of this new knowledge with respect to optimal clinical care have been carefully considered by the CTS Panel and the conclusions are presented in the current document. Highlights of this update include new epidemiological information on mortality and prevalence of COPD, which charts its emergence as a major health problem for women; a new section on common comorbidities in COPD; an increased emphasis on the meaningful benefits of combined pharmacological and nonpharmacological therapies; and a new discussion on the prevention of acute exacerbations. A revised stratification system for severity of airway obstruction is proposed, together with other suggestions on how best to clinically evaluate individual patients with this complex disease. The results of the largest randomized clinical trial ever undertaken in COPD have recently been published, enabling the Panel to make evidence-based recommendations on the role of modern pharmacotherapy. The Panel hopes that these new practice guidelines, which reflect a rigorous analysis of the recent literature, will assist caregivers in the diagnosis and management of this common condition.